Indirect effect of temperature on fish population abundances through phenological changes - Kuczynski, Lucie; Chevalier, Mathieu; Laffaille, Pascal; Legrand, Marion; Grenouillet, Gaël (PLOS ONE, 2017)
In response to climate change, earlier phenological events have been reported for a large range of taxa such that phenological shifts are considered as one of the fingerprints of the effect of climate change on organisms. Evidence further suggests that changes in the timing of phenological events might decouple biotic interactions due to differential phenological adjustment among interacting species, ultimately leading to population declines. Nonetheless, few studies have investigated how climate-driven changes in the timing of phenological events influence population abundances. In this study, we investigated how two environmental variables known to influence the migration timing of freshwater fish (i.e. water discharge and temperature) directly or indirectly influenced abundances of 21 fish species using daily time series gathered at four sites located in France over a period spanning from 9 to 21 years. We found no evidence for long-term trends in migration timing or fish abundances over time. Using piecewise structural equation models, we demonstrate that inter-annual variations in abundances were driven by inter-annual variations in temperature through variations in migration timing. Overall, our results suggest that climate change may concomitantly influence different biological aspects (e.g. phenology, abundance) of fish species. We argue that considering different responses to climate change is paramount if we are to improve our understanding of how organisms and populations are influenced by climate change in order to set-up efficient conservation strategies.